Role of 6-O-α-maltosyl-β-cyclodextrin in lysosomal cholesterol deprivation in Npc1-deficient Chinese hamster ovary cells. (2nd January 2018) - Okada, Yasuyo; Ueda, Erika; Kondo, Yuki; Ishitsuka, Yoichi; Irie, Tetsumi; Higashi, Taishi; Motoyama, Keiichi; Arima, Hidetoshi; Matuso, Muneaki; Higaki, Katsumi; Ohno, Kousaku; Nishikawa, Junichi; et al.
Abstract: We aimed to investigate whether 6- O -α-maltosyl-β-cyclodextrin (Mal-βCD) is incorporated into cells and lysosomes during the release of unesterified cholesterol in Npc1- deficient Chinese hamster ovary (CHO) cells ( Npc1 KO cells) and CHO-JP17 cells (JP17 cells). Internalization of Mal-βCD in cells and lysosomes and extracellular release of lysosomal unesterified cholesterol were demonstrated by LC/MS/MS and LC/MS, respectively. Internalization of Mal-βCD was greater in Npc1 KO cells than in JP17 cells. The majority of internalized Mal-βCD in both cell types was metabolized by lysosomal α-glucosidase to 6- O -α-D-glucosyl-β-cyclodextrin (Glc-βCD). However, Mal-βCD did not directly enter the lysosomes prepared from cell homogenates. Mal-βCD-treated Npc1 KO cells and JP17 cells both released Mal-βCD and Glc-βCD, together with unesterified cholesterol, out of cells. The release of unesterified cholesterol by Mal-βCD in Npc1 KO cells was much greater than that in JP17 cells. This study is the first to report the influx of Mal-βCD into the lysosomes of Npc1 KO cells and JP17 cells, followed by generation of Glc-βCD, and the efflux of Mal-βCD/Glc-βCD and unesterified cholesterol to the extracellular fluid, based on the quantitative LC/MS analysis. Graphical abstract: Highlights: 6- O -α-Maltosyl(Mal)-βCD reduces lysosomal cholesterol storage of Npc1 -mutant cells. Mal-βCD is endocytosed, and accumulated in the lysosome of Npc1- mutant cells. Mal-βCD accumulated in the lysosome is partly metabolized to Glc-βCD. Mal/Glc-βCD and cholesterol are released from the lysosome and Npc1- mutant cells. Intracellular behavior of Mal-βCD and cholesterol is quantitated by LC/MS.